Enhancing Vocabulary Intervention for Kindergarten Students: Strategic Integration of Semantically Related and Embedded Word Review - Zipoli, Richard P.; Coyne, Michael D.; McCoach, D. Betsy (Remedial and Special Education, 2011)
Two approaches to systematic word review were integrated into an 18-week program of extended vocabulary instruction with kindergarten students from three high-need urban schools. Words in the embedded and semantically related review conditions received systematic and distributed review. In the embedded review condition, brief word definitions were integrated into the narratives of multiple storybooks. In the semantically related review condition, in-depth word review with explicit emphasis on semantic features and associations was provided during extension activities. Systematic review resulted in an almost twofold increase in target word learning. Embedded review was effective and time efficient, whereas semantically related review was time intensive but resulted in higher levels of word learning. There was a significant gain in Peabody Picture Vocabulary Test—III standard scores following the intervention.
Keywords: dept.cmd; peer-reviewed

Effects of a Supplemental Vocabulary Intervention on the Word Knowledge of Kindergarten Students at Risk for Language and Literacy Difficulties - Loftus, Susan M.; Coyne, Michael D.; McCoach, D. Betsy; Zipoli, Richard; Pullen, Paige C. (Learning Disabilities Research & Practice, 2010)
The purpose of this study was to examine the effectiveness of a vocabulary intervention designed to supplement research–based classroom vocabulary instruction, implemented with students who may be at risk for language and learning difficulties. Participants included 43 kindergarten students who received research–based classroom vocabulary instruction. Students with the 20 lowest scores on the Peabody Picture Vocabulary Test–III administered at pretest received additional small–group supplemental vocabulary intervention. Results of within–subjects comparisons indicated that, overall, at–risk students made greater gains in word knowledge on target words that received the supplemental intervention as compared to words that received only classroom–based instruction. In addition, at–risk students who received the supplemental intervention demonstrated word–learning gains that approached those of their peers who received classroom instruction alone. Implications along with limitations of the current study and directions for future research are discussed.
Keywords: dept.cmd; peer-reviewed

Effective Strategies for Teaching Reading Comprehension. - Coyne, M. D.; Chard, D. J.; Zipoli, R. P.; Ruby, M. F. (Effective Teaching Strategies that Accommodate Diverse Learners, 2010)
Keywords: dept.cmd

Initiating Safe Oral Feeding in Critically Ill Intensive Care and Step-Down Unit Patients Based on Passing a 3-Ounce (90 Milliliters) Water Swallow Challenge - Leder, Steven B.; Suiter, Debra M.; Warner, Heather L.; Kaplan, Lewis J. (Journal of Trauma and Acute Care Surgery, 2011)
Background: Pulmonary aspiration is a leading cause of nosocomial infection in the intensive care unit (ICU) and step-down unit (SDU). A key goal is to identify patients who exhibit increased aspiration risk before beginning oral alimentation. This study investigated the success of recommending specific oral diets to ICU and SDU patients based on passing a 3-oz water swallow challenge. Methods: A referral-based sample of 401 ICU and 92 SDU patients were prospectively analyzed. Amount of liquid and food ingested at the next day's meal 12 hours to 24 hours after passing a 3-oz challenge and specific diet recommendations were accessed electronically from oral intake information entered on each participant's daily care sheets. Drinking and eating success, clinically evident aspiration events, and accuracy of diet order recommendations were recorded. Care providers were blinded to the purpose of the study. Results: All 401 ICU and 92 SDU patients were successfully drinking thin liquids and eating 12 hours to 24 hours after passing a 3-oz challenge. Mean volume of liquid ingested at the next day's meal was 360 mL ± 181.2 mL for ICU and 356.4 mL ± 173.5 mL for SDU patients. Percent of meal eaten ranged from 10% to 100%. Patient care sheets indicated specific diet recommendations were followed with 100% accuracy. Conclusions: Successfully recommending specific oral diets for ICU and SDU patients based on passing a 3-oz water swallow challenge was supported. Importantly, when a simple bedside 3-oz challenge administered by a trained provider is passed, specific diet recommendations can be made safely and confidently without the need for further objective dysphagia testing.
Keywords: dept.cmd; peer-reviewed

Effect of Presence/Absence of a Nasogastric Tube in the Same Person on Incidence of Aspiration - Fattal, Michael; Suiter, Debra M.; Warner, Heather L.; Leder, Steven B. (Otolaryngology–Head and Neck Surgery, 2011)
Objective. To determine what effect, if any, the presence or absence of a nasogastric (NG) tube in the same person had on the incidence of anterograde aspiration. Design. Case series with planned data collection. Setting. Large, urban, tertiary care teaching hospital. Subjects and Methods. Referred sample of 62 consecutively enrolled adult inpatients for fiber-optic endoscopic evaluation of swallowing (FEES). Group 1 (n = 21) had either small-bore (n = 13) or large-bore (n = 8) NG tubes already in place and had a FEES first with the NG tube in place and a second FEES after NG tube removal. Group 2 (n = 41) did not have an NG tube and had a FEES first without an NG tube and a second FEES after placement of a small-bore NG tube. Time between FEES was approximately 5 minutes. Patients were tested with thin liquid and puree food consistencies. Occurrence of aspiration for each consistency dependent on the presence or absence of an NG tube was recorded. Results. There were no significant differences (P > .05) in aspiration status for both liquid and puree consistencies in the same person dependent on presence or absence of either a small-bore or large-bore NG tube. Conclusions. Since objective swallowing evaluation (eg, FEES) can be performed with an NG tube in place, it is not necessary to remove an NG tube to evaluate for aspiration. Similarly, there is no contraindication to leaving an NG tube in place to supplement oral alimentation until nutritional requirements are achieved.
Keywords: dept.cmd; peer-reviewed

Deaf-Blind - McCullagh, Jennifer; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Screening Test for Auditory Processing Disorders - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Pediatric Speech Intelligibility Test - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Otitis Media - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Hearing - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Dichotic Listening - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Deafness - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Cochlea - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Brainstem Audiometry - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Auditory Brainstem Response, ABR - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Speaking and Reading in Two Languages: On the Identification of Reading and Language Disabilities in Spanish-Speaking English Learners - Francis, David J.; Rojas, Raúl; Gusewski, Svenja; Santi, Kristi L.; Khalaf, Shiva; Hiebert, Lindsey; Bunta, Ferenc (New Directions for Child and Adolescent Development, 2019)
Articles in this issue examine (1) the primary sources of variability in reading and language achievement among Spanish-speaking English learners (ELs) in the United States, (2) the extent to which poor performance at the end of grade 2 is identifiable in developmental trajectories beginning in kindergarten, (3) the relations among core reading constructs of phonological awareness and decoding in both English and Spanish and the factors that affect their relationship, (4) the performance of different approaches to identification and the factors that influence how well they work, as well as (5) the growing literature focused on intervention for reading problems in this population. This article examines the literature on language minority students and disability identification and analyzes a large-scale longitudinal dataset (>4,000 ELs; >15,000 observations) to systematically characterize and describe the oral language and reading development of Spanish-speaking children designated as ELs from kindergarten to second grade, considering a range of factors that may potentially contribute to that characterization and its relation to academic performance. This systematic characterization should facilitate the development of an empirical basis for a theoretically grounded framework of typical development in ELs in order to more precisely identify those children with language and learning disabilities.
Keywords: dept.cmd; peer-reviewed

Moving Forward by Looking Back: Understanding Why Some Spanish-Speaking English Learners Fall Behind - Rojas, Raúl; Hiebert, Lindsey; Gusewski, Svenja; Francis, David J. (New Directions for Child and Adolescent Development, 2019)
This study investigated early indicators of Spanish-speaking English learners (ELs) at risk for reading difficulties at the end of Grade 2 by examining their early bilingual oral language development, taking into account language of academic instruction. Standardized measures of reading and narrative samples were collected in English and Spanish from kindergarten to Grade 2 from 1,243 ELs primarily instructed in English or Spanish. Conditional growth curve models yielded four primary findings of reading and oral language development. First, ELs with low reading achievement at the end of Grade 2 demonstrated early reading difficulties during kindergarten. Second, although ELs demonstrated overall higher reading achievement in their instructed language, this difference decreased over time. Third, ELs with low reading achievement at the end of Grade 2 demonstrated lower oral language skills in each language over time. Fourth, ELs demonstrated overall higher oral language skills in their instructed language, yet these differences varied over time. The study provided a detailed description of the longitudinal relations among the bilingual reading and oral language skills of Spanish-speaking ELs during the early school years. These findings help to inform the processes of early identification and intervention for Spanish-speaking ELs who are likely to demonstrate reading achievement difficulties.
Keywords: dept.cmd; peer-reviewed

Assessment of Code-Based Reading Skills by Speech-Language Pathologists. - Zipoli, Richard P. (2018)
The purpose of the sabbatical leave was to (a) review the extensive body of research and clinical literature on code-based reading difficulties and (b) prepare a journal manuscript and conference presentation to disseminate clinical information to a wide audience of school-based speech-language pathologists.
Keywords: dept.cmd; faculty_collection; sabbatical_report

Multimodal communication training in aphasia: A pilot study - Purdy, M.; Van Dyke, J.A. (Journal of Medical Speech-Language Pathology, 2011)
Management of patients with aphasia often focuses on training nonverbal augmentative communication strategies; however, these strategies frequently do not generalize to natural situations. The limited success may be because training was not sufficient to produce an integrated multimodal semantic representation. The purpose of this study was to examine whether simultaneous training of stimuli in both verbal and nonverbal modalities would solidify the links within the semantic network and improve switching among modalities as needed in conversation. Two individuals with severe aphasia participated in 6 to 8 hours of Multimodal Communication Training (MCT), during which they conveyed a concept by verbalizing, gesturing, writing, and drawing. After practice with all modalities for a single concept, a new concept was introduced. Results showed that one participant increased conveyance of concepts on the functional communication task using a variety of modalities. Although some improvement was seen with the second participant, his overall performance remained poor, likely because of a greater impairment in semantic knowledge. After a brief period of semantic training, the second participant demonstrated additional gains. Thus, MCT may serve to increase switching among verbal and nonverbal modalities in individuals with intact semantic representations, thereby increasing the likelihood that individuals will use an alternative method to communicate. Copyright © 2011 Delmar Cengage Learning.
Keywords: AAC; Aphasia; Cognition; Multimodality; Treatment; adult; aged; article; ataxic aphasia; case report; communication skill; concept formation; cortical sensory aphasia; dept.cmd; disease severity; drawing; gesture; human; male; multimodal communication training; priority journal; semantic memory; task performance; verbalization; writing; ⛔ No DOI found

Comparison of reading performance in fluent and non-fluent aphasia - Purely, M.; Newman, D. (2011)
Keywords: dept.cmd

Parsing pragmatics - Rivers, K.O.; Hyter, Y.D.; DeJarnette, G. (ASHA Leader, 2012)
Keywords: dept.cmd

More than words - Wallace, S.; Purdy, M. (ASHA Leader, 2013)
Keywords: dept.cmd

An uncommon case: Cleft palate, respiratory compromise, and klippel-feil anomaly - Langevin, K.M.; Mabry, K.; Castiglione, C. (Plastic Surgical Nursing, 2014)
Keywords: Cervical Vertebrae; Cleft Palate; Female; Humans; Infant, Newborn; Klippel-Feil Syndrome; Spinal Fusion; cervical vertebra; cleft palate; complication; dept.cmd; female; genetics; human; newborn; procedures; spine fusion

Identification of Conductive Hearing Loss in Young Infants Using Tympanometry and Wideband Reflectance. - Prieve, Beth; Vander Werff, Kathy; Preston, Jonathan; Georgantas, Lea (Ear and Hearing, 2013)
Objective: The goal of the study was to evaluate the effectiveness of tympanometry and wideband reflectance (WBR) in detecting conductive hearing loss (CHL) in young infants., Methods: Type of hearing loss was determined using auditory brainstem response using air- and bone-conducted tone bursts in 84 ears from 70 infants (median age = 10 weeks). Of these 84 ears, 60 are included in the current analysis: 43 with normal hearing (NH) and 17 with CHL. Tympanometry was measured using probe tone frequencies of 226, 678, and 1000 Hz. Tympanograms were evaluated in two ways: (1) Acoustic middle ear admittance (Ya, in millimhos); and (2) two-category classification (normal/abnormal), as described by Baldwin (2006). Measures of Ya were evaluated in two ways: by admittance-magnitude tympanograms and calculated admittance magnitude from subcomponents (conductance and susceptance). WBR was measured in response to a chirp stimulus after probe calibration. WBR was analyzed into thirteen 1/3 octave bands. Tests for statistical differences for two-category classification were analyzed using Chi-squared and Ya, and WBR were analyzed using repeated-measures analyses of variances. Cohen's d and likelihood ratios were computed for comparison with statistically significant differences., Results: Ya measured with 678- and 1000 Hz probe tones was significantly different between ears with CHL and NH. Two-category classification of tympanograms using a 1000 Hz probe tone was significantly different between ears with CHL and NH. Neither two-category classification nor Ya was significantly different between ears identified with CHL and NH using a 226 Hz probe tone. WBR was significantly higher in the frequency bands 800 to 2500 Hz and in the frequency band centered at 6300 Hz in infants with CHL. Effect sizes (Cohen's d) were greater than 2 for several WBR frequency bands and Ya measured with 1000 Hz probe tones. The results were similar for calculations of Ya from admittance-magnitude and subcomponent tympanograms. Positive likelihood ratios for WBR ranged between 8.1 and 38, and those for Ya using 1000 Hz ranged between 12.5 and 32., Conclusions: CHL in young infants can be detected well with WBR or tympanometry using probe frequencies of 678 and 1000 Hz., (C) 2013 by Lippincott Williams & Wilkins
Keywords: Acoustic Impedance Tests; Acoustic Stimulation; Evoked Potentials, Auditory, Brain Stem; Female; Hearing Loss, Conductive; Hearing Tests; Humans; Infant; Infant, Newborn; Likelihood Functions; Male; Sensitivity and Specificity; acoustic impedance; article; auditory stimulation; conduction deafness; dept.cmd; evoked brain stem auditory response; female; hearing test; human; infant; male; methodology; newborn; sensitivity and specificity; statistical model

Out of the mouths of babes: vocal production in infant siblings of children with ASD - Paul, Rhea; Fuerst, Yael; Ramsay, Gordon J.; Chawarska, Kasia; Klin, Ami (Journal of Child Psychology and Psychiatry, 2010)
Background: Younger siblings of children with autism spectrum disorders (ASD) are at higher risk for acquiring these disorders than the general population. Language development is usually delayed in children with ASD. The present study examines the development of pre-speech vocal behavior in infants at risk for ASD due to the presence of an older sibling with the disorder. Methods: Infants at high risk (HR) for ASD and those at low risk, without a diagnosed sibling (LR), were seen at 6, 9, and 12 months as part of a larger prospective study of risk for ASD in infant siblings. Standard clinical assessments were administered, and vocalization samples were collected during play with mother and a standard set of toys. Infant vocal behavior was recorded and analyzed for consonant inventory, presence of canonical syllables, and of non-speech vocalizations, in a cross-sectional design. Children were seen again at 24 months for provisional diagnosis. Results: Differences were seen between risk groups for certain vocal behaviors. Differences in vocal production in the first year of life were associated with outcomes in terms of autistic symptomotology in the second year. Conclusions: Early vocal behavior is a sensitive indicator of heightened risk for autistic symptoms in infants with a family history of ASD.
Keywords: *Child Development Disorders, Pervasive/px [Psychology]; *Infant Behavior/px [Psychology]; *Language Development; *Siblings/px [Psychology]; *Speech; Autism; Child Development Disorders, Pervasive; Child Development Disorders, Pervasive/ge [Genetics]; Child, Preschool; Cross-Sectional Studies; Female; Humans; Infant; Infant Behavior; Language Development; Male; Prospective Studies; Risk Factors; Siblings; Speech; Speech Acoustics; Speech Production Measurement; article; autism; child behavior; cross-sectional study; dept.cmd; female; genetics; human; infant; infant siblings; language development; male; preschool child; prospective study; psychological aspect; risk factor; sibling; speech; speech analysis; vocalization

Aphasia, alexia, and agraphia - Purdy, Mary (Reference Module in Neuroscience and Biobehavioral Psychology Encyclopedia of Mental Health (Second Edition), 2016)
Aphasia is a general language disorder resulting from brain damage, and alexia and agraphia are specific impairments in reading and writing, respectively. This article describes the symptoms associated with each disorder, the subtypes of each impairment, and the common causes. Assessment and management approaches consistent with the World Health Organization International Classification of Functioning (WHO-ICF) are briefly reviewed. © 2016 Elsevier Inc. All rights reserved.
Keywords: Acquired language disorders; Agraphia; Alexia; Aphasia; Assessment; Communication disorder; Dysgraphia; Dyslexia; Dysphasia; Management; WHO-ICF; dept.cmd

Intensive multimodal communication treatment for people with chronic aphasia - Purdy, Mary; Wallace, Sarah E. (Aphasiology, 2016)
Background: Clinicians often teach persons with aphasia (PWA) non-verbal strategies to compensate for reduced verbal communication. The manner in which they teach the strategies may have an impact on how well PWA generalise and use the strategies. Previously, multimodal communication treatment (MCT) taught multiple modalities simultaneously. While participants demonstrated some increase in the flexible use of strategies, many communication breakdowns continued to occur. Recent research suggests that intensive treatment protocols result in the greatest increase in skills.Aims: The purpose of this study was to determine whether intensive (2-3hours/day, 5 days/week, for 2 weeks) multimodality communication training for aphasia resulted in increased successful use of verbal and non-verbal communication modalities as well as increased successful communicative repairs during structured communication tasks.Methods & Procedures: Three participants with chronic aphasia completed four baseline sessions, 10 treatment sessions across two phases (i.e., five sessions per phase), and three post-treatment sessions.Outcomes & Results: Two of the three participants demonstrated gains in the acquisition of non-verbal strategies during training and increased use of strategies on a referential communication task.Conclusions: Although MCT delivered intensely resulted in increased use of non-verbal modalities for two out of three participants, the results were similar to that achieved through the use of a non-intensive treatment protocol. Therefore, future research is needed to examine other potential modifications to maximise the gains people with aphasia receive from multimodal interventions.
Keywords: Article; Cognitive Linguistic Quick Test; accuracy; adult; aphasia; case report; cognitive function test; communication; dept.cmd; disease severity; hemiparesis; human; intensive treatment; interrater reliability; male; middle aged; multimodality communication training; nonverbal communication; outcome assessment; peer-reviewed; physiotherapy; strategy usage; training

Perception of speech sounds in school-aged children with speech sound disorders - Preston, Jonathan L.; Irwin, Julia R.; Turcios, Jacqueline (Seminars in Speech and Language, 2015)
Children with speech sound disorders may perceive speech differently than children with typical speech development. The nature of these speech differences is reviewed with an emphasis on assessing phoneme-specific perception for speech sounds that are produced in error. Category goodness judgment, or the ability to judge accurate and inaccurate tokens of speech sounds, plays an important role in phonological development. The software Speech Assessment and Interactive Learning System, which has been effectively used to assess preschoolers' ability to perform goodness judgments, is explored for school-aged children with residual speech errors (RSEs). However, data suggest that this particular, task may not be sensitive to perceptual differences in school-aged children. The need for the development of clinical tools for assessment of speech perception in school-aged children with RSE is highlighted, and clinical suggestions are provided.
Keywords: Child; Female; Humans; Male; Phonetics; Speech; Speech Perception; Speech Sound Disorder; Speech sound disorder; assessment; child; dept.cmd; dept.psy; female; human; male; pathophysiology; phonetics; speech; speech perception; speech sound disorder

Ways of examining speech acts in young african american children: considering inside-out and outside-in approaches. - Dejarnette, Glenda; Rivers, Kenyatta O; Hyter, Yvette D (Topics in Language Disorders, 2015)
To develop a framework for further study of pragmatic behavior in young children from African American English (AAE) speaking backgrounds, one aspect of pragmatic behavior is explored in this article, specifically, speech acts. The aims of this article are to (1) examine examples of how external taxonomies (i.e., an “etic” or “outside-in” approach) have been applied to the speech act behavior of AAE child speakers and to note that etic approaches alone do not identify cultural characteristics that influence the presentation of speech acts in this population; (2) conceptualize a culture-sensitive framework where components of AAE speech act behaviors can be identified as gleaned from existing linguistic research; and (3) explain the utility of analyses of speech act behavior using taxonomies that have emerged from the cultural language style of AAE speakers, that is, an “emic” or “inside-out” approach.
Keywords: English speakers; communicative functions; dept.cmd; language behavior; pragmatic behavior; speech acts; young African American

Pragmatic language of african american children and adolescents: A systematic synthesis of the literature. - Hyter, Yvette D; Rivers, Kenyatta O; Dejarnette, Glenda (Topics in Language Disorders, 2015)
Purpose: A systematic review and synthesis was performed on published articles and dissertations produced between 1970 and 2013 that focused on selected pragmatic language behaviors of African American children and adolescents. Methods: Electronic databases and hand searches of articles located in the databases were used to identify the published articles and dissertations. Each article or dissertation was reviewed by at least 2 of the authors to determine whether it met the criteria for inclusion in this study. Selected observations of the documents that met criteria for inclusion were recorded on the Primary Research Appraisal Tool (PRAT; DeJarnette, Hyter, & Rivers, 2012), a data gathering and analysis framework developed by the authors specifically for this systematic synthesis. Results: The literature search resulted in 92 research articles and dissertations, 37 of which were eliminated because they did not meet all of the inclusion criteria. The documents that met our inclusion criteria focused primarily on the structure and/or content of narrative discourse rather than speech acts, other forms of discourse (e.g., conversation, expository), and presupposition/perspective taking skills. Six major themes identified in the major findings are used to summarize studies reviewed for this systematic synthesis. Conclusions: We (a) explain the current state of knowledge about African American pragmatic language behaviors, (b) explain major findings and implications of the extant literature in this topical area and how it may inform speech-language pathology practice, and (c) identify directions for future research on pragmatic language of African American children and adolescents.
Keywords: African American; communication functions; dept.cmd; discourse; pragmatic language; presupposition; speech acts; systematic review and synthesis; theory of mind

Phonological complexity in school-aged children who stutter and exhibit a language disorder. - Wolk, Lesley; LaSalle, Lisa R (Journal of fluency disorders, 2015)
PURPOSE: The Index of Phonological Complexity and the Word Complexity Measure are two measures of the phonological complexity of a word. Other phonological measures such as phonological neighborhood density have been used to compare stuttered versus fluent words. It appears that in preschoolers who stutter, the length and complexity of the utterance is more influential than the phonetic features of the stuttered word. The present hypothesis was that in school-age children who stutter, stuttered words would be more phonologically complex than fluent words, when the length and complexity of the utterance containing them is comparable. School-age speakers who stutter were hypothesized to differ from those with a concomitant language disorder., METHODS: Sixteen speakers, six females and ten males (M age=12;3; Range=7;7 to 19;5) available from an online database, were divided into eight who had a concomitant language disorder (S+LD) and eight age- and sex-matched speakers who did not (S-Only)., RESULTS: When all stuttered content words were identified, S+LD speakers produced more repetitions, and S-Only speakers produced more inaudible sound prolongations. When stuttered content words were matched to fluent content words and when talker groups were combined, stuttered words were significantly (p<=0.01) higher in both the Index of Phonological Complexity and the Word Complexity Measure and lower in density ("sparser") than fluent words., CONCLUSIONS: Results corroborate those of previous researchers. Future research directions are suggested, such as cross-sectional designs to evaluate developmental patterns of phonological complexity and stuttering plus language disordered connections., EDUCATIONAL OBJECTIVES: The reader will be able to: (a) Define and describe phonological complexity; (b) Define phonological neighborhood density and summarize the literature on the topic; (c) Describe the Index of Phonological Complexity (IPC) for a given word; (d) Describe the Word Complexity Measure (WCM) for a given word; (e) Summarize two findings from the current study and describe how each relates to studies of phonological complexity and fluency disorders. Copyright © 2014 Elsevier Inc. All rights reserved.
Keywords: *Language; *Linguistics; *Phonetics; *Stuttering; Adolescent; Adult; Article; Child; Concomitant disorders; Female; Humans; Language; Language disorders; Linguistics; Male; Phonetics; Phonological complexity; Schools; Speech; Speech Production Measurement; Stuttering; adolescent; adult; child; controlled study; data base; dept.cmd; female; fluency disorder; human; language; language disability; linguistics; male; phoneme; phonetics; school; school child; speech; speech analysis; stuttering

Development of an audiovisual speech perception app for children with autism spectrum disorders - Irwin, Julia; Preston, Jonathan; Brancazio, Lawrence; D'Angelo, Michael; Turcios, Jacqueline (Clinical Linguistics & Phonetics, 2015)
Perception of spoken language requires attention to acoustic as well as visible phonetic information. This article reviews the known differences in audiovisual speech perception in children with autism spectrum disorders (ASD) and specifies the need for interventions that address this construct. Elements of an audiovisual training program are described. This researcher-developed program delivered via an iPad app presents natural speech in the context of increasing noise, but supported with a speaking face. Children are cued to attend to visible articulatory information to assist in perception of the spoken words. Data from four children with ASD ages 8-10 are presented showing that the children improved their performance on an untrained auditory speech-in-noise task.
Keywords: Attention; Audiovisual Aids; Audiovisual app; Autism spectrum disorder; Child; Child Development Disorders, Pervasive; Comprehension; Humans; Lipreading; Male; Mobile Applications; Pattern Recognition, Visual; Phonetics; Semantics; Speech Perception; Speech perception; attention; audiovisual aid; child; comprehension; dept.cmd; dept.hls; dept.psy; human; lip reading; male; mobile application; pattern recognition; phonetics; psychology; semantics; speech perception

Ultrasound visual feedback treatment and practice variability for residual speech sound errors - Preston, Jonathan L.; McCabe, Patricia; Rivera-Campos, Ahmed; Whittle, Jessica L.; Landry, Erik; Maas, Edwin (Journal of Speech Language and Hearing Research, 2014)
Purpose: The goals were to (a) test the efficacy of a motor-learning-based treatment that includes ultrasound visual feedback for individuals with residual speech sound errors and (b) explore whether the addition of prosodic cueing facilitates speech sound learning. Method: A multiple-baseline, single-subject design was used, replicated across 8 participants. For each participant, 1 sound context was treated with ultrasound plus prosodic cueing for 7 sessions, and another sound context was treated with ultrasound but without prosodic cueing for 7 sessions. Sessions included ultrasound visual feedback as well as non-ultrasound treatment. Word-level probes assessing untreated words were used to evaluate retention and generalization. Results: For most participants, increases in accuracy of target sound contexts at the word level were observed with the treatment program regardless of whether prosodic cueing was included. Generalization between onset singletons and clusters was observed, as was generalization to sentence-level accuracy. There was evidence of retention during posttreatment probes, including at a 2-month follow-up. Conclusion: A motor-based treatment program that includes ultrasound visual feedback can facilitate learning of speech sounds in individuals with residual speech sound errors.
Keywords: Child; Cues; Feedback, Sensory; Female; Humans; Male; Phonetics; Speech; Speech Sound Disorder; Speech Therapy; Ultrasonography; Young Adult; association; child; dept.cmd; diagnostic imaging; echography; female; human; male; pathophysiology; phonetics; physiology; procedures; sensory feedback; speech; speech sound disorder; speech therapy; young adult; ⚠️ Invalid DOI

Glutamate and choline levels predict individual differences in reading ability in emergent readers - Pugh, Kenneth R.; Frost, Stephen J.; Rothman, Douglas L.; Hoeft, Fumiko; Tufo, Stephanie N. Del; Mason, Graeme F.; Molfese, Peter J.; Mencl, W. Einar; Grigorenko, Elena L.; Landi, Nicole; Preston, Jonathan L.; Jacobsen, Leslie; et al. (The Journal of Neuroscience, 2014)
Reading disability is a brain-based difficulty in acquiring fluent reading skills that affects significant numbers of children. Although neuroanatomical and neurofunctional networks involved in typical and atypical reading are increasingly well characterized, the underlying neurochemical bases of individual differences in reading development are virtually unknown. The current study is the first to examine neurochemistry in children during the critical period in which the neurocircuits that support skilled reading are still developing. In a longitudinal pediatric sample of emergent readers whose reading indicators range on a continuum from impaired to superior, we examined the relationship between individual differences in reading and reading-related skills and concentrations of neurometabolites measured using magnetic resonance spectroscopy. Both continuous and group analyses revealed that choline and glutamate concentrations were negatively correlated with reading and related linguistic measures in phonology and vocabulary (such that higher concentrations were associated with poorer performance). Correlations with behavioral scores obtained 24 months later reveal stability for the relationship between glutamate and reading performance. Implications for neurodevelopmental models of reading and reading disability are discussed, including possible links of choline and glutamate to white matter anomalies and hyperexcitability. These findings point to new directions for research on gene-brain-behavior pathways in human studies of reading disability. © 2014 the authors.
Keywords: 4 aminobutyric acid; Aspartic Acid; Brain; Child; Choline; Decoding; Dyslexia; Female; Glutamic Acid; Humans; Individual differences; Individuality; Learning; MRS; Magnetic Resonance Spectroscopy; Male; Phonetics; Phonological processing; Predictive Value of Tests; Reading; Reading disability; Vocabulary; article; behavior; child; choline; decoding; dept.cmd; female; gamma-Aminobutyric Acid; glutamic acid; human; human experiment; individual differences; language ability; linguistics; male; nerve cell differentiation; nerve excitability; normal human; nuclear magnetic resonance spectroscopy; phonetics; phonological processing; priority journal; reading; reading disability; school child; speech

Structural brain differences in school-age children with residual speech sound errors. - Preston, Jonathan L; Molfese, Peter J; Mencl, W Einar; Frost, Stephen J; Hoeft, Fumiko; Fulbright, Robert K; Landi, Nicole; Grigorenko, Elena L; Seki, Ayumi; Felsenfeld, Susan; Pugh, Kenneth R (Brain and Language, 2014)
The purpose of the study was to identify structural brain differences in school-age children with residual speech sound errors. Voxel based morphometry was used to compare gray and white matter volumes for 23 children with speech sound errors, ages 8;6-11;11, and 54 typically speaking children matched on age, oral language, and IQ. We hypothesized that regions associated with production and perception of speech sounds would differ between groups. Results indicated greater gray matter volumes for the speech sound error group relative to typically speaking controls in bilateral superior temporal gyrus. There was greater white matter volume in the corpus callosum for the speech sound error group, but less white matter volume in right lateral occipital gyrus. Results may indicate delays in neuronal pruning in critical speech regions or differences in the development of networks for speech perception and production. Copyright © 2013 Elsevier Inc. All rights reserved.
Keywords: *Brain/pa [Pathology]; *Language Development Disorders/pa [Pathology]; *Phonetics; *Speech Perception; Brain; Child; Children; Humans; Language Development Disorders; Magnetic Resonance Imaging; Phonetics; Speech Perception; Speech sound disorders; Speech sound errors; Structural MRI; article; brain region; brain size; child; clinical article; controlled study; corpus callosum; dept.cmd; female; gray matter; human; male; neuroanatomy; occipital gyrus; school child; speech articulation; speech perception; speech sound disorder; speech sound error; superior temporal gyrus; voxel based morphometry; white matter

Neurophysiology of speech differences in childhood apraxia of speech - Preston, Jonathan L; Molfese, Peter J; Gumkowski, Nina; Sorcinelli, Andrea; Harwood, Vanessa; Irwin, Julia; Landi, Nicole (Developmental Neuropsychology, 2014)
Event-related potentials (ERPs) were recorded during a picture naming task of simple and complex words in children with typical speech and with childhood apraxia of speech (CAS). Results reveal reduced amplitude prior to speaking complex (multisyllabic) words relative to simple (monosyllabic) words for the CAS group over the right hemisphere during a time window thought to reflect phonological encoding of word forms. Group differences were also observed prior to production of spoken tokens regardless of word complexity during a time window just prior to speech onset (thought to reflect motor planning/programming). Results suggest differences in pre-speech neurolinguistic processes.
Keywords: Adolescent; Apraxias; Child; Evoked Potentials; Female; Humans; Linguistics; Male; Neurophysiology; Speech; adolescent; apraxia; article; child; comparative study; dept.cmd; dept.psy; evoked response; female; human; linguistics; male; neurophysiology; pathophysiology; physiology; speech

A multimodal communication program for aphasia during inpatient rehabilitation: A case study. - Wallace, Sarah E; Purdy, Mary; Skidmore, Elizabeth (NeuroRehabilitation, 2014)
BACKGROUND: Communication is essential for successful rehabilitation, yet few aphasia treatments have been investigated during the acute stroke phase. Alternative modality use including gesturing, writing, or drawing has been shown to increase communicative effectiveness in people with chronic aphasia. Instruction in alternative modality use during acute stroke may increase patient communication and participation, therefore resulting in fewer adverse situations and improved rehabilitation outcomes., OBJECTIVE: The study purpose was to explore a multimodal communication program for aphasia (MCPA) implemented during acute stroke rehabilitation. MCPA aims to improve communication modality production, and to facilitate switching among modalities to resolve communication breakdowns., METHODS: Two adults with severe aphasia completed MCPA beginning at 2 and 3 weeks post onset a single left-hemisphere stroke. Probes completed during each session allowed for evaluation of modality production and modality switching accuracy., RESULTS: Participants completed MCPA (10 and 14 treatment sessions respectively) and their performance on probes suggested increased accuracy in the production of various alternate communication modalities. However, increased switching to an alternate modality was noted for only one participant., CONCLUSIONS: Further investigation of multimodal treatment during inpatient rehabilitation is warranted. In particular, comparisons between multimodal and standard treatments would help determine appropriate interventions for this setting.
Keywords: *Aphasia/px [Psychology]; *Aphasia/rh [Rehabilitation]; *Communication; *Communication Aids for Disabled; *Communication Disorders/px [Psychology]; *Communication Disorders/rh [Rehabilitation]; Aphasia; Article; Communication; Communication Aids for Disabled; Communication Disorders; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychomotor Performance; Stroke; Stroke Rehabilitation; Stroke/co [Complications]; Stroke/px [Psychology]; Treatment Outcome; acute rehabilitation; adult; aphasia; case report; cerebrovascular accident; communication aid; complication; dept.cmd; female; hospital patient; human; interpersonal communication; left hemisphere; male; mental performance; middle aged; multimodal treatment; neuropsychological test; psychological rating scale; psychology; psychomotor performance; rehabilitation care; stroke; treatment outcome

Ultrasound biofeedback treatment for persisting childhood apraxia of speech - Preston, Jonathan L.; Brick, Nickole; Landi, Nicole (American Journal of Speech-language Pathology, 2013)
Purpose: The purpose of this study was to evaluate the efficacy of a treatment program that includes ultrasound biofeedback for children with persisting speech sound errors associated with childhood apraxia of speech (CAS). Method: Six children ages 9-15 years participated in a multiple baseline experiment for 18 treatment sessions during which treatment focused on producing sequences involving lingual sounds. Children were cued to modify their tongue movements using visual feedback from real-time ultrasound images. Probe data were collected before, during, and after treatment to assess word-level accuracy for treated and untreated sound sequences. As participants reached preestablished performance criteria, new sequences were introduced into treatment. Results: All participants met the performance criterion (80% accuracy for 2 consecutive sessions) on at least 2 treated sound sequences. Across the 6 participants, performance criterion was met for 23 of 31 treated sequences in an average of 5 sessions. Some participants showed no improvement in untreated sequences, whereas others showed generalization to untreated sequences that were phonetically similar to the treated sequences. Most gains were maintained 2 months after the end of treatment. The percentage of phonemes correct increased significantly from pretreatment to the 2-month follow-up. Conclusion: A treatment program including ultrasound biofeedback is a viable option for improving speech sound accuracy in children with persisting speech sound errors associated with CAS.
Keywords: Adolescent; Apraxias; Articulation; Biofeedback, Psychology; Child; Childhood apraxia of speech; Children; Cues; Efficacy; Feedback, Sensory; Follow-Up Studies; Humans; Intervention; Male; Phonetics; Speech; Speech Disorders; Speech Therapy; Speech sound disorders; Tongue; Treatment Outcome; Ultrasonic Therapy; adolescent; apraxia; article; articulation; association; child; childhood apraxia of speech; children; clinical trial; dept.cmd; echography; efficacy; follow up; human; intervention; male; methodology; pathophysiology; phonetics; physiology; psychophysiology; sensory feedback; speech; speech disorder; speech sound disorders; speech therapy; tongue; treatment outcome; ultrasound therapy

Toward improved spectral measures of /s/: results from adolescents - Koenig, Laura L.; Shadle, Christine H.; Preston, Jonathan L.; Mooshammer, Christine R. (Journal of Speech Language and Hearing Research, 2013)
Purpose: This article introduces theoretically driven acoustic measures of /s/ that reflect aerodynamic and articulatory conditions. The measures were evaluated by assessing whether they revealed expected changes over time and labiality effects, along with possible gender differences suggested by past work. Method: Productions of /s/ were extracted from various speaking tasks from typically speaking adolescents (6 boys, 6 girls). Measures were made of relative spectral energies in low-(550-3000 Hz), mid-(3000-7000 Hz), and high-frequency regions (7000-11025 Hz); the mid-frequency amplitude peak; and temporal changes in these parameters. Spectral moments were also obtained to permit comparison with existing work. Results: Spectral balance measures in low-mid and mid-high frequency bands varied over the time course of /s/, capturing the development of sibilance at mid-fricative along with showing some effects of gender and labiality. The mid-frequency spectral peak was significantly higher in nonlabial contexts, and in girls. Temporal variation in the mid-frequency peak differentiated +/- labial contexts while normalizing over gender. Conclusions: The measures showed expected patterns, supporting their validity. Comparison of these data with studies of adults suggests some developmental patterns that call for further study. The measures may also serve to differentiate some cases of typical and misarticulated /s/.
Keywords: Acoustics; Adolescent; Adolescents; Development; Female; Humans; Lip; Male; Phonetics; Reference Values; Sex Characteristics; Speech; Speech Acoustics; Speech production; Verbal Behavior; acoustics; adolescent; adolescents; article; comparative study; dept.cmd; development; female; human; lip; male; phonetics; reference value; sexual development; speech; speech production; verbal behavior

Preschool speech error patterns predict articulation and phonological awareness outcomes in children with histories of speech sound disorders. - Preston, Jonathan L; Hull, Margaret; Edwards, Mary Louise (American journal of speech-language pathology, 2013)
Purpose: To determine if speech error patterns in preschoolers with speech sound disorders (SSDs) predict articulation and phonological awareness (PA) outcomes almost 4 years later. Method: Twenty-five children with histories of preschool SSDs (and normal receptive language) were tested at an average age of 4;6 (years;months) and were followed up at age 8;3. The frequency of occurrence of preschool distortion errors, typical substitution and syllable structure errors, and atypical substitution and syllable structure errors was used to predict later speech sound production, PA, and literacy outcomes. Results: Group averages revealed below-average schoolage articulation scores and low-average PA but ageappropriate reading and spelling. Preschool speech error patterns were related to school-age outcomes. Children for whom >10% of their speech sound errors were atypical had lower PA and literacy scores at school age than children who produced <10% atypical errors. Preschoolers who produced more distortion errors were likely to have lower school-age articulation scores than preschoolers who produced fewer distortion errors. Conclusion: Different preschool speech error patterns predict different school-age clinical outcomes. Many atypical speech sound errors in preschoolers may be indicative of weak phonological representations, leading to long-term PA weaknesses. Preschoolers' distortions may be resistant to change over time, leading to persisting speech sound production problems. © American Speech-Language-Hearing Association.
Keywords: *Articulation Disorders/di [Diagnosis]; *Language Tests; *Phonetics; *Speech; *Speech Articulation Tests; Awareness; Child; Child Language; Child, Preschool; Female; Follow-Up Studies; Humans; Language Disorders/di [Diagnosis]; Literacy; Male; Outcomes; Phonological awareness; Predictive Value of Tests; Psycholinguistics; Reading; Speech Production Measurement; Speech Sound Disorder; Speech production; Speech sound disorders; dept.cmd

The relationship between phonological and auditory processing and brain organization in beginning readers - Pugh, Kenneth R.; Landi, Nicole; Preston, Jonathan L.; Mencl, W. Einar; Austin, Alison C.; Sibley, Daragh; Fulbright, Robert K.; Seidenberg, Mark S.; Grigorenko, Elena L.; Constable, R. Todd; Molfese, Peter; Frost, Stephen J. (Brain and Language, 2013)
We employed brain-behavior analyses to explore the relationship between performance on tasks measuring phonological awareness, pseudoword decoding, and rapid auditory processing (all predictors of reading (dis)ability) and brain organization for print and speech in beginning readers. For print-related activation, we observed a shared set of skill-correlated regions, including left hemisphere temporoparietal and occipitotemporal sites, as well as inferior frontal, visual, visual attention, and subcortical components. For speech-related activation, shared variance among reading skill measures was most prominently correlated with activation in left hemisphere inferior frontal gyrus and precuneus. Implications for brain-based models of literacy acquisition are discussed. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Awareness; Brain; Brain Mapping; Child; Child, Preschool; Decoding; FMRI; Female; Humans; Individual differences; Male; Phonological awareness; Photic Stimulation; Psychomotor Performance; Rapid auditory processing; Reading; Speech; Speech Perception; Thalamus; Visual Perception; article; attention; child; dept.cmd; female; frontal lobe; hearing; human; human experiment; inferior frontal gyrus; left hemisphere; male; neurophysiology; normal human; occipital lobe; parietal lobe; phonetics; precuneus; preschool child; printing; reading; school child; speech; task performance; temporal lobe; visual cortex; word recognition

Auditory cortical processing in noise in younger and older adults - Mccullagh, Jennifer; Shinn, Jennifer B (Hearing, Balance and Communication, 2013)
Objective: A common clinical complaint among older adults is difficulty hearing in noise, even in those with normal or near-normal peripheral hearing sensitivity. Researchers have demonstrated behavioral hearing in noise deficits in older adults, but to date limited evidence, particularly objective, exists elucidating the effects of age on auditory cortical processing in noise. The purpose of this investigation was to explore age related differences in auditory cortical processing at multiple signal-to-noise ratios (SNRs). Study design: Twenty normal-hearing young adults and 15 normal-hearing older adults participated in the study. Late auditory evoked potential (N1 and P2) latencies and amplitudes were measured in quiet and at three signal-to-noise ratios (SNRs) (+ 20, + 10, and 0 SNR). Repeated measures analyses of variance (ANOVA) were utilized to determine if statistically significant differences existed. Results: Significant group by listening condition interactions existed for N1 and P2 amplitudes. P2 latencies were significantly longer for the older adult group compared to the younger adult group. In addition, N1 and P2 amplitudes were significantly smaller for the younger adult group compared to the older adult group. Conclusion: Results suggest a possibly greater reduction in the synchronous neuronal response from quiet to noisy conditions in older adults than in younger adults. © 2013 Informa Healthcare.
Keywords: Aging; Auditory late potentials; Hearing in noise; N1; P2; dept.cmd; peer-reviewed

Functional brain activation differences in school-age children with speech sound errors: speech and print processing - Preston, Jonathan L.; Felsenfeld, Susan; Frost, Stephen J.; Mencl, W. Einar; Fulbright, Robert K.; Grigorenko, Elena L.; Landi, Nicole; Seki, Ayumi; Pugh, Kenneth R. (Journal of Speech Language and Hearing Research, 2012)
Purpose: To examine neural response to spoken and printed language in children with speech sound errors (SSE). Method: Functional magnetic resonance imaging was used to compare processing of auditorily and visually presented words and pseudowords in 17 children with SSE, ages 8; 6[years; months] through 10; 10, with 17 matched controls. Results: When processing spoken words and pseudowords, the SSE group showed less activation than typically speaking controls in left middle temporal gyrus. They also showed greater activation than controls in several cortical and subcortical regions (e. g., left superior temporal gyrus, globus pallidus, insula, fusiform, and bilateral parietal regions). In response to printed words and pseudowords, children with SSE had greater activation than controls in regions including bilateral fusiform and anterior cingulate. Some differences were found in both speech and print processing that that may be associated with children with SSE failing to show common patterns of task-induced deactivation and/or attentional resource allocation. Conclusion: Compared with controls, children with SSE appear to rely more on several dorsal speech perception regions and less on ventral speech perception regions. When processing print, numerous regions were observed to be activated more for the SSE group than for controls.
Keywords: Brain; Cerebral Cortex; Child; Female; Functional magnetic resonance imaging (fMRI); Globus Pallidus; Gyrus Cinguli; Humans; Language Development Disorders; Magnetic Resonance Imaging; Male; Parietal Lobe; Phonetics; Photic Stimulation; Print processing; Reading; Speech; Speech Perception; Speech perception; Speech sound errors; Temporal Lobe; Visual Cortex; article; brain; brain cortex; child; cingulate gyrus; dept.cmd; female; globus pallidus; human; language disability; male; nuclear magnetic resonance imaging; parietal lobe; pathophysiology; phonetics; photostimulation; physiology; reading; speech; speech perception; temporal lobe; visual cortex

Auditory cortical processing in noise in normal-hearing young adults - Mccullagh, Jennifer; Musiek, Frank E; Shinn, Jennifer B (Audiological Medicine, 2012)
Objective: The ability to hear in background noise is related to the processing of the incoming acoustic signal in the peripheral auditory system as well as the central auditory nervous system (CANS). Electrophysiological tests have the ability to demonstrate the underlying neural integrity of the CANS, but to date a lack of literature exists demonstrating the effects of background noise on auditory cortical potentials. Therefore, the purpose of this investigation was to systematically investigate the effects of white noise on tone burst-evoked late auditory evoked potentials (N1, P2, and P3) in normal hearing young adults. Study Design: Twenty young-adult normal-hearing individuals served as subjects. A comparison of the late auditory evoked potentials (N1, P2, and P3) was made at multiple signal-to-noise ratios (SNRs) (quiet, + 20, + 10, 0). N1, P2, and P3 were elicited and both amplitude and latency were measured for each of the potentials. A standard oddball paradigm with binaural stimulation was used to evoke the potentials. Repeated Measures Analyses of Variance (ANOVA) were conducted for both the experimental factors of amplitude and latency with within subjects factors of condition (quiet, + 20, + 10, 0). Results: Results indicated no significant differences in N1, P2, or P3 amplitude or latency between the quiet and + 20 SNR condition; however, at poorer SNRs significant N1, P2, and P3 amplitude and/or latency differences were observed. Conclusion: The results indicate a change in higher-order neural function related to the presence of increased noise in the environment. © 2012 Informa Healthcare.
Keywords: Auditory evoked potentials; Central auditory processing; Hearing in noise; Late auditory evoked potentials; N1; P2; P3; Signal to noise ratio; adult; amplitude modulation; article; auditory nervous system; auditory stimulation; central nervous system; controlled study; dept.cmd; electrophysiology; evoked auditory response; female; hearing; human; human experiment; late auditory evoked potential; male; normal human; priority journal; sensory system electrophysiology; signal noise ratio

Searching for Potocki–Lupski syndrome phenotype: A patient with language impairment and no autism - Ercan-Sencicek, A. Gulhan; Wright, Nicole R. Davis; Frost, Stephen J.; Fulbright, Robert K.; Felsenfeld, Susan; Hart, Lesley; Landi, Nicole; Mencl, W. Einar; Sanders, Stephan J.; Pugh, Kenneth R.; State, Matthew W.; Grigorenko, Elena L. (Brain & Development, 2011)
Potocki-Lupski syndrome (PTLS; OMIM 610883) is a genomic syndrome that arises as a result of a duplication of 17p11.2. Although numerous cases of individuals with PTLS have been presented in the literature, its behavioral characterization is still ambiguous. We present a male child with a de novo dup(17)(p11.2p11.2) and he does not possess any autistic features, but is characterized by severe speech and language impairment. In the context of the analyses of this patient and other cases of PTLS, we argue that the central feature of the syndrome appears to be related to diminished speech and language capacity, rather than the specific social deficits central to autism. © 2011.
Keywords: 17p11.2; Autistic Disorder; Child; Chromosomes, Human, Pair 17; Humans; Inv(8)(q21.3-q24.1); Language Disorders; Language and speech impairment; Male; Phenotype; Potocki Lupski syndrome; Potocki-Lupski syndrome; Smith-Magenis Syndrome; academic achievement; adaptive behavior; article; case report; child; child development; chromosome 17p; chromosome duplication; clinical feature; dept.cmd; functional magnetic resonance imaging; genetic disorder; human; intelligence; language development; language disability; male; malformation syndrome; school child

Phonetic variability in residual speech sound disorders exploration of subtypes - Preston, Jonathan L.; Koenig, Laura L. (Topics in Language Disorders, 2011)
Purpose: To explore whether subgroups of children with residual speech sound disorders (R-SSDs) can be identified through multiple measures of token-to-token phonetic variability (changes in one spoken production to the next). Method: Children with R-SSDs were recorded during a rapid multisyllabic picture naming task and an oral diadochokinetic task. Transcription-based and acoustic measures of token-to-token variability were derived. Articulation accuracy and general indices of language skills were measured as well. Results: Low correlations were observed between transcription-based and acoustic measures of phonetic variability, and among the acoustic measures themselves. Children who were the most variable on one measure were not necessarily highly variable on other measures. Transcription-based measures of variability were associated with language skills. Conclusions: Measures of phonetic variability did not identify children in the sample as consistently high or low. Data do not support the notion that clear subgroups based on phonetic variability can be reliably identified in children with R-SSDs. The link between highly variable phonetic output (quantified by transcription-based measures) and lower language skills requires further exploration.
Keywords: acoustic analysis; dept.cmd; phonetic variability; residual speech sound disorders

Identifying residual speech sound disorders in bilingual children: A japanese-english case study - Preston, Jonathan L.; Seki, Ayumi (American Journal of Speech-language Pathology, 2011)
Purpose: To describe (a) the assessment of residual speech sound disorders (SSDs) in bilinguals by distinguishing speech patterns associated with second language acquisition from patterns associated with misarticulations and (b) how assessment of domains such as speech motor control and phonological awareness can provide a more complete understanding of SSDs in bilinguals. Method: A review of Japanese phonology is provided to offer a context for understanding the transfer of Japanese to English productions. A case study of an 11-year-old is presented, demonstrating parallel speech assessments in English and Japanese. Speech motor and phonological awareness tasks were conducted in both languages. Results: Several patterns were observed in the participant's English that could be plausibly explained by the influence of Japanese phonology. However, errors indicating a residual SSD were observed in both Japanese and English. A speech motor assessment suggested possible speech motor control problems, and phonological awareness was judged to be within the typical range of performance in both languages. Conclusion: Understanding the phonological characteristics of the native language can help clinicians recognize speech patterns in the second language associated with transfer. Once these differences are understood, patterns associated with a residual SSD can be identified. Supplementing a relational speech analysis with measures of speech motor control and phonological awareness can provide a more comprehensive understanding of a client's strengths and needs.
Keywords: Articulation; Assessment; Bilingualism; Residual speech sound disorders; Speech motor control; dept.cmd

Attentional regulation in young twins with probable stuttering, high nonfluency, and typical fluency. - Felsenfeld, Susan; van Beijsterveldt, Catharina Eugenie Maria; Boomsma, Dorret Irene (Journal of Speech, Language, and Hearing Research, 2010)
PURPOSE: Using a sample of 20,445 Dutch twins, this study examined the relationship between speech fluency and attentional regulation in children. A secondary objective was to identify etiological overlap between nonfluency and poor attention using fluency-discordant twin pairs., METHOD: Three fluency groups were created at age 5 using a parent questionnaire: (a) probable stuttering (PS; N=826; 4.0%), highly nonfluent (HNF; N=547; 2.7%), and typically fluent (TF; N=19,072; 93%). Multiple scales assessing attention, primarily self-regulation/inhibition, were obtained from both parents when children were ages 5 and 7 and from teachers when children were age 7., RESULTS: When compared with the TF controls, both the PS and HNF children received higher (i.e., more problematic) scores on parental attention ratings at both ages (p<.002). Effect sizes were moderate for both groups. Teacher and parent ratings were generally comparable. The discordant co-twin analyses suggested that nonfluency and attention were influenced by potentially overlapping genetic and shared environmental factors., CONCLUSIONS: The liability to express both high nonfluency and problems with self-regulation/inhibition may arise from a common set of pathogenic mechanisms. This supports emerging models of stuttering, which propose that poor fluency may be part of a broader network of impaired self-regulatory processes.
Keywords: *Attention Deficit Disorder with Hyperactivity/co [Complications]; *Attention/ph [Physiology]; *Executive Function/ph [Physiology]; *Speech/ph [Physiology]; *Stuttering/co [Complications]; Attention; Attention Deficit Disorder with Hyperactivity; Attention Deficit Disorder with Hyperactivity/px [Psychology]; Case-Control Studies; Child; Child, Preschool; Cohort Studies; Diseases in Twins; Executive Function; Female; Humans; Inhibition (Psychology); Inhibition, Psychological; Longitudinal Studies; Male; Nonfluency; Reference Values; Self Efficacy; Speech; Speech Production Measurement; Stuttering; Stuttering/pp [Physiopathology]; Stuttering/px [Psychology]; Twins; article; attention; attention deficit disorder; case control study; child; cohort analysis; comparative study; dept.cmd; executive function; female; human; inhibition (psychology); longitudinal study; male; pathophysiology; physiology; preschool child; psychological aspect; reference value; self concept; speech; speech analysis; stuttering; twins; ⚠️ Invalid DOI

Impact of chromosome 4p-Syndrome on communication and expressive language skills: A preliminary investigation - Marshall, Althea T (Language, speech, and hearing services in schools, 2010)
PURPOSE: The purpose of this investigation was to examine the impact of Chromosome 4p- syndrome on the communication and expressive language phenotype of a large cross-cultural population of children, adolescents, and adults., METHOD: A large-scale survey study was conducted and a descriptive research design was used to analyze quantitative and qualitative data regarding the communication and expressive language manifestations of 200 children, youth, and adults from 16 countries and Puerto Rico who had been diagnosed with 4p conditions, including Wolf-Hirschhorn syndrome (WHS), Pitt-Rogers-Danks syndrome (PRDS), Proximal 4p Deletion syndrome, and complex chromosomal rearrangements associated with 4p-., RESULTS: Individuals with Chromosome 4p- syndrome represent a heterogeneous population with complex phenotypic profiles. The majority of the participants exhibited communication and expressive language skills below the 36-month developmental functioning level. A relatively small cohort of the study population exhibited advanced expressive language skills, a finding not reported in the professional literature., CONCLUSION: Results broaden the spectrum of expressive language skills associated with Chromosome 4p- syndrome and highlight the communication potential of a subset of individuals with 4p abnormalities for development of advanced language structures. It is hypothesized that the largest 4p deletion, which includes the 4p16.3 band and contiguous gene regions, results in the most severely affected expressive language phenotype.
Keywords: *Chromosome Disorders/ge [Genetics]; *Chromosome Disorders/px [Psychology]; *Chromosomes, Human, Pair 4; *Communication; *Language; Adolescent; Adult; Child; Child, Preschool; Chromosome Disorders; Chromosome Disorders/co [Complications]; Chromosomes, Human, Pair 4; Cohort Studies; Communication; Communication Disorders; Communication Disorders/co [Complications]; Communication Disorders/ge [Genetics]; Cross-Cultural Comparison; Developmental disabilities; Female; Genetics; Humans; Infant; Language; Male; Middle Aged; Phenotype; Syndrome; Wolf Hirschhorn syndrome; Wolf-Hirschhorn Syndrome; Wolf-Hirschhorn Syndrome/co [Complications]; Wolf-Hirschhorn Syndrome/ge [Genetics]; Wolf-Hirschhorn Syndrome/px [Psychology]; Young Adult; adolescent; adult; article; child; chromosome 4; chromosome disorder; cohort analysis; communication disorder; complication; cultural factor; dept.cmd; female; genetics; human; infant; interpersonal communication; language; male; middle aged; phenotype; preschool child; psychological aspect; psychology; syndrome; young adult

Bivariate genetic analyses of stuttering and nonfluency in a large sample of 5-Year-Old twins - Beijsterveldt, Catharina Eugenie Maria Van; Felsenfeld, Susan; Boomsma, Dorret I (Journal of Speech Language and Hearing Research, 2010)
Purpose: Behavioral genetic studies of speech fluency have focused on participants who present with clinical stuttering. Knowledge about genetic influences on the development and regulation of normal speech fluency is limited. The primary aims of this study were to identify the heritability of stuttering and high nonfluency and to assess the relative contribution of genetic and environmental factors to the correlation between these 2 fluency phenotypes. Method: Information on 6 specific speech fluency behaviors was obtained by maternal report for over 10,500 5-year-old Dutch twin pairs. Results: Genetic analyses revealed that both fluency phenotypes were moderately heritable, with heritability estimates of 42% and 45% for probable stuttering and high nonfluency, respectively. Shared environmental factors were also significant, explaining 44% of the individual differences in probable stuttering and 32% in nonfluency. For both phenotypes, the magnitude of the genetic and environmental influences did not differ between boys and girls. The overlap between the 2 traits was substantial (tetrachoric correlation was .72). A bivariate genetic analysis showed that this overlap was due to both overlapping genetic and environmental influences. Conclusions: These findings provide a foundation to justify further studies in normal fluency control, a scientific area that has received little cross-disciplinary attention.
Keywords: Child Language; Child, Preschool; Cohort Studies; Environment; Female; Heritability; Humans; Male; Models, Genetic; Multivariate Analysis; Netherlands; Nonfluency; Phenotype; Probability; Questionnaires; Sex Factors; Speech Disorders; Stuttering; Twins; Twins, Dizygotic; Twins, Monozygotic; article; biological model; cohort analysis; dept.cmd; dizygotic twins; environment; female; genetics; human; language development; male; monozygotic twins; multivariate analysis; phenotype; preschool child; probability; questionnaire; sex difference; speech disorder; stuttering; twins

Impact and implications of word-finding difficulties in adolescents on listening comprehension assessment - Newman, Diana B (Communication Disorders Quarterly, 2010)
This investigation examined the listening comprehension (LC) performance of two groups of adolescent struggling readers, one group with word-finding difficulties (WFD) and one with no word-finding difficulties (NWFD). Of interest was whether the expressive language difficulties of the WFD group would interfere with their success on a LC assessment that requires oral responses to complete. Findings indicated that whereas the performance of the WFD group was comparable with the NWFD group when LC was measured using a multiple-choice response format, their performance was significantly poorer when LC was measured using an open-ended verbal response format, suggesting that learners' WFD could interfere with their success on such assessments. Practical implications of these findings for the assessment of LC as part of adolescents' reading evaluations are discussed. © 2010 Hammill Institute on Disabilities.
Keywords: adolescent; article; child; comprehension; controlled study; dept.cmd; human; language disability; listening comprehension; mental performance; multiple choice test; priority journal; reading; reading assessments; school child; task performance; word finding difficulty; word recognition; word-finding

Delayed Language Development in Preschool Children - Weiss, Deborah; Paul, Rhea (The Handbook of Language and Speech Disorders, 2010)
Keywords: "delayed language development" (DLD); "specific language impairment" (SLI); Delayed language development in preschool children; Developing language stage; Intervention for children with DLD; Language development and departure from typical acquisition in preschool children; Linguistic Characteristics of Children with DLD; Speech disorders; Language disorders; Communicative disorders; Speech-language pathologist (SLP)-primarily because their speech contains frequent articulation errors; Targets for vocabulary training for preschoolers with DLD; delayed language development in preschool children; dept.cmd; developing language stage; faculty_collection; intervention for children with DLD; language development and departure from typical acquisition in preschool children; speech-language pathologist (SLP) - primarily because their speech contains frequent articulation errors; targets for vocabulary training for preschoolers with DLD; “delayed language development” (DLD); “specific language impairment” (SLI)

Diagnostic and treatment outcomes for an adolescent with left functional hemispherectomy - McCullagh, Jennifer; Dilaj, K (Adult Audiology Casebook, 2019)
Keywords: dept.cmd; faculty_collection

Dichotic listening training following neurological injury in adults: a pilot study - Purdy, Mary; McCullagh, Jennifer (Hearing, Balance and Communication, 2019)
Purpose: Injury to the dominant left brain hemisphere can lead to specific language deficits such as aphasia, or to the cognitive processes that support language such as attention and working memory. Language is heavily supported through the auditory modality, which is a key area of deficit in acquired language disorders, and recovery of auditory processing is a prerequisite to recovery of other language modalities. A specific auditory processing deficit that has been identified following neurologic injury is dichotic listening. Some researchers have suggested that dichotic listening can be strengthened through the use of a dichotic listening training paradigm, although the impact of this training for adults with neurological injury is unknown. The purpose of this study was to determine whether dichotic listening training improved dichotic listening performance as well as auditory comprehension in individuals with neurological injuries.Method: Five individuals with a history of acquired language deficits who met specific inclusion and exclusion criteria participated in the dichotic listening training for four to six weeks. Dichotic listening and language comprehension skills were evaluated pre- and post-training.Results: Results indicated all participants progressed through a range of dichotic listening tasks during training, and four of the five individuals improved on at least one of the dichotic listening tests post-treatment. All of the participants demonstrated some improvement in auditory processing/comprehension of complex commands.Conclusions: Dichotic listening training has the potential to positively influence dichotic listening and auditory comprehension skills in adults with neurological injury.
Keywords: Article; Dichotic listening; adult; auditory processing; auditory processing disorder; auditory rehabilitation; brain injury; cerebrovascular accident; clinical article; comprehension; dept.cmd; dichotic listening; distortion product otoacoustic emission; hearing impairment; human; language ability; language disability; male; neurologic; peer-reviewed; pilot study; priority journal; pure tone audiometry; treatment; tympanometry

College Access, Success and Equity for Students on the Autism Spectrum. - Accardo, Amy L; Bean, Kimberly; Cook, Barbara; Gillies, Ann; Edgington, Rebecca; Kuder, S Jay; Bomgardner, Estyr M (Journal of autism and developmental disorders, 2019)
College may be considered a gateway to success, yet access to college is limited for young adults with autism. Given the research recommendations to elicit student experiences and to communicate among universities to improve college access, success, and equity, the present study examined the questions: What factors are perceived as pathways to success or barriers to success by college students on the autism spectrum? What university provided accommodations and/or support services do they prefer? Participants from four universities completed surveys and semi-structured interviews. Findings from the multi-university study suggest the need to provide transition planning and systematic non-academic social and emotional supports from the start of the college experience as well as specific training for faculty, staff, and peers.
Keywords: *Academic Success; *Autism Spectrum Disorder/rh [Rehabilitation]; *Mainstreaming, Education/sn [Statistics & Numerical Data]; *Universities/sn [Statistics & Numerical Data]; Academic Success; Accommodations; Adolescent; Article; Autism Spectrum Disorder; Autism Spectrum Disorder/px [Psychology]; Autism spectrum disorder; College; Female; Humans; Mainstreaming, Education; Male; Mental health; Students; Students/px [Psychology]; Students/sn [Statistics & Numerical Data]; Universities; University; Young Adult; academic success; adolescent; adult; autism; college; college student; dept.cmd; dept.sed; disability; executive function; female; financial management; follow up; health equity; human; longitudinal study; male; mental health care; motivation; peer-reviewed; priority journal; psychology; self concept; semi structured interview; social network; social support; student; student attitude; university; young adult

Adult swallow screening and clinical swallow evaluations - Suiter, Debra; Warner, Heather L. (Assessing and treating dysphagia: A lifespan perspective, 2019)
The definitive educational guide on the diagnosis and management of dysphagia across the full age continuumDysphagia presentation and treatment differs at various stages of life. Assessing and Treating Dysphagia: A Lifespan Perspective reflects significant knowledge and pearls from esteemed adult and pediatric swallowing disorders experts. Debra Suiter and Memorie Gosa have compiled a book of unique depth and breadth with contributions from communication science experts including speech-language pathologists and physicians. The textbook provides comprehensive coverage of swallowing disorders from birth to old age, including clinical, professional, and cultural ethical considerations.Key HighlightsAnatomy and physiology of swallowing, and compensatory, postural, and rehabilitation strategiesAdult and pediatric specific chapters on swallow screenings, clinical evaluations, and technologies such as videofluroscopic, fiberoptic endoscopic, and high-resolution manometryPediatric-specific dysphagia related to premature birth, craniofacial syndromes, congenital heart disease, and cerebral palsyAdult-specific dysphagia related to neurodegenerative disease, stroke, traumatic brain injury, head and neck cancer, esophageal disease, pulmonary disease, and end of lifeThis is the only textbook on the market featuring complete coverage of the diagnosis and management of dysphasia across the lifespan. With content following Master's-level course curriculum, this is essential reading for graduate students as well as practicing clinicians in the fields of otolaryngology and speech language pathology.This book includes complimentary access to a digital copy on https://medone.thieme.com.
Keywords: dept.cmd

Reading comprehension treatment in aphasia: A systematic review - Purdy, Mary; Coppens, Patrick; Madden, Elizabeth Brookshire; Mozeiko, Jennifer; Patterson, Janet; Wallace, Sarah E.; Freed, Donald (Aphasiology, 2019)
Background: Reading difficulties often present as a consequence of aphasia. The specific nature of reading deficits varies widely in manifestation, and the cause of these deficits may be the result of a phonological, lexical semantic, or cognitive impairment. Several treatments have been developed to address a range of impairments underlying reading difficulty.Aims: The purpose of this review is to describe the current research on reading comprehension treatments for persons with aphasia, assess the quality of the research, and summarize treatment outcomes.Methods & Procedures: A systematic review of the literature was conducted based on a set of a priori questions, inclusion/exclusion criteria, and pre-determined search parameters. Results were summarized according to treatment type, methodologic rigor, and outcomes.Outcomes & Results: Fifteen studies meeting criteria were identified. A variety of reading comprehension treatments was implemented including: oral reading, strategy-based, cognitive treatment, and hierarchical reading treatments. Quality ratings were highly variable, ranging from 3 to 9 (on a 12-point scale). Overall, 14 of the 18 individuals for whom individual data were provided demonstrated some degree of improvement (oral reading 4/5 participants, strategy based 4/6, and cognitive treatment 6/7). Gains were also evident for hierarchical reading treatment administered to participant groups via computer; however, the degree to which improvement reached statistical significance varied among studies.Conclusions: Reading comprehension treatments have the potential to improve reading comprehension ability in persons with aphasia; however, outcomes were variable within and among treatment methods. We suggest focusing future research on factors such as participant candidacy and treatment intensity using increased methodological rigor.
Keywords: Aphasia; Mini Mental State Examination; Review; agraphia; aphasia; certification; cognition; cognitive defect; communication skill; comprehension; deep learning; dementia; dept.cmd; dyslexia; episodic memory; human; interrater reliability; language test; motivation; peer-reviewed; phonetics; psychometry; quality of life; randomized controlled trial (topic); reading; reading comprehension; scientific literature; social hierarchy; stamen; systematic review; treatment; treatment outcome; word recognition; working memory

Relationship Between Laryngeal Sensation, Length of Intubation, and Aspiration in Patients with Acute Respiratory Failure. - Borders, James C; Fink, Daniel; Levitt, Joseph E; McKeehan, Jeffrey; McNally, Edel; Rubio, Alix; Scheel, Rebecca; Siner, Jonathan M; Taborda, Stephanie Gomez; Vojnik, Rosemary; Warner, Heather; White, S David; et al. (Dysphagia, 2019)
Dysphagia is common in hospitalized patients post-extubation and associated with poor outcomes. Laryngeal sensation is critical for airway protection and safe swallowing. However, current understanding of the relationship between laryngeal sensation and aspiration in post-extubation populations is limited. Acute respiratory failure patients requiring intensive care unit admission and mechanical ventilation received a Flexible Endoscopic Evaluation of Swallowing (FEES) within 72 h of extubation. Univariate and multivariable analyses were performed to examine the relationship between laryngeal sensation, length of intubation, and aspiration. Secondary outcomes included pharyngolaryngeal secretions, pneumonia, and diet recommendations. One-hundred and three patients met inclusion criteria. Fifty-one patients demonstrated an absent laryngeal adductor reflex (LAR). Altered laryngeal sensation correlated with the presence of secretions (p = 0.004). There was a significant interaction between the LAR, aspiration, and duration of mechanical ventilation. Altered laryngeal sensation was significantly associated with aspiration on FEES only in patients with a shorter length of intubation (p = 0.008). Patients with altered laryngeal sensation were prescribed significantly more restricted liquid (p = 0.03) and solid (p = 0.001) diets. No relationship was found between laryngeal sensation and pneumonia. There is a high prevalence of laryngeal sensory deficits in mechanically ventilated patients post-extubation. Altered laryngeal sensation was associated with secretions, aspiration, and modified diet recommendations especially in those patients with a shorter length of mechanical ventilation. These results demonstrate that laryngeal sensory abnormalities impact the development of post-extubation dysphagia.
Keywords: *Intubation, Intratracheal/ae [Adverse Effects]; *Laryngeal Diseases/et [Etiology]; *Pneumonia, Aspiration/et [Etiology]; *Sensation Disorders/et [Etiology]; Acute Disease; Acute respiratory failure; Article; Critical illness; Deglutition; Deglutition disorders; FEES; Female; Flexible Endoscopic Evaluation of Swallowing; Humans; Intubation, Intratracheal; Laryngeal Diseases; Laryngeal Diseases/pp [Physiopathology]; Laryngeal sensation; Larynx; Larynx/pp [Physiopathology]; Male; Middle Aged; Pneumonia, Aspiration; Prospective Studies; Respiratory Insufficiency; Sensation Disorders; Sensation Disorders/pp [Physiopathology]; Time Factors; absent laryngeal adductor reflex; acute disease; acute respiratory failure; adult; adverse event; artificial ventilation; aspiration; aspiration pneumonia; bodily secretions; clinical outcome; clinical trial; cohort analysis; controlled study; critical illness; dept.cmd; dietary intake; disease association; dysphagia; endotracheal intubation; extubation; female; hospital admission; human; intensive care; larynx; larynx disorder; lung aspiration; major clinical study; male; middle aged; multicenter study; nutritional requirement; outcome assessment; pathophysiology; peer-reviewed; pharyngolaryngeal secretions; pneumonia; prescription; prevalence; priority journal; prospective study; reflex disorder; respiratory failure; sensory dysfunction; time factor

Evaluation of Swallow Function Post-Extubation: Is It Necessary to Wait 24 Hours?. - Leder, Steven B; Warner, Heather L; Suiter, Debra M; Young, Nwanmegha O; Bhattacharya, Bishwajit; Siner, Jonathan M; Davis, Kimberly A; Maerz, Linda L; Rosenbaum, Stanley H; Marshall, Peter S; Pisani, Margaret A; Siegel, Mark D; et al. (The Annals of otology, rhinology, and laryngology, 2019)
BACKGROUND: Post-extubation dysphagia is associated with an increased incidence of nosocomial pneumonias, longer hospitalizations, and higher re-intubation rates. The purpose of this study was to determine if it is necessary to delay swallow evaluation for 24 hours post-extubation., METHODS: A prospective investigation of swallowing was conducted at 1, 4, and 24 hours post-extubation to determine if it is necessary to delay swallow evaluation following intubation. Participants were 202 adults from 5 different intensive care units (ICU)., RESULTS: A total of 166 of 202 (82.2%) passed the Yale Swallow Protocol at 1 hour post-extubation, with an additional 11 (177/202; 87.6%) at 4 hours, and 8 more (185/202; 91.6%) at 24 hours. Only intubation duration >=4 days was significantly associated with nonfunctional swallowing., CONCLUSIONS: We found it is not necessary to delay assessment of swallowing in individuals who are post-extubation. Specifically, the majority of patients in our study (82.2%) passed a swallow screening at 1 hour post-extubation.
Keywords: *Airway Extubation; *Deglutition Disorders/di [Diagnosis]; *Speech-Language Pathology/mt [Methods]; Adult; Aged; Aged, 80 and over; Airway Extubation; Article; Deglutition Disorders; Female; Humans; Intensive Care Units; Male; Middle Aged; Prospective Studies; Respiration, Artificial; Respiratory Insufficiency; Respiratory Insufficiency/th [Therapy]; Speech-Language Pathology; Time Factors; Young Adult; adult; aged; artificial ventilation; clinical assessment; clinical evaluation; clinical practice; controlled study; deglutition; deglutition disorders; dept.cmd; dysphagia; endotracheal intubation; extubation; female; hospitalization; human; intensive care unit; major clinical study; male; mental health; middle aged; oral alimentation; peer-reviewed; priority journal; procedures; prospective study; respiratory failure; speech disorder; speech language pathologist; swallowing; swallowing assessment; therapy delay; time factor; treatment duration; very elderly; young adult

Auditory p300 in noise in younger and older adults - McCullagh, Jennifer; Shinn, Jennifer B. (Journal of the American Academy of Audiology, 2018)
Background: Older adults often report difficulty hearing in background noise which is not completely attributable to peripheral hearing loss. Although age-related declines in cognition and hearing in back-ground noise occur, the underlying age-related changes in processing of auditory stimuli in background noise has yet to be fully understood. The auditory P300 has the potential to elucidate the effects of age on auditory and cognitive processing of stimuli in background noise, but additional research is warranted. Purpose: The purpose of this study was to investigate age-related differences in cognitive processing of auditory stimuli by evoking the auditory P300 at multiple signal-to-noise ratios (SNRs). Research Design: A two-group, repeated measures study design was used. Study Sample: A convenience sample of 35 participants, 15 older adults (mean age of 66.4 yr) and 20 younger adults (mean age of 21.1 yr), participated in the study. All participants had negative otologic and neurological histories. Data Collection and Analysis: The auditory P300 was evoked using an oddball paradigm with 500 (frequent) and 1000 Hz (target) tonal stimuli in quiet and in the presence of background noise at +20, +10, and 0 SNRs. P300 amplitudes and latencies were measured in each condition for every participant. Repeated measures analyses of variance were conducted for the amplitude and latency measures of the P300 for each group. Results: Results from this study demonstrated P300 latencies were significantly longer in older adults in noise at the most challenging condition (0 SNR) compared with the quiet condition and between the +10 SNR and 0 SNR conditions. Although older adults had significantly longer P300 latencies compared with younger adults, no significant group by listening condition interaction existed. No significant P300 amplitude differences were found for group, noise, or group x listening condition interactions. Conclusions: Results provide evidence that auditory cortical processing, regardless of age, is poorer at more difficult SNRs. However, results also demonstrate that older adults perform significantly poorer than younger adults. This supports the notion that some degree of age-related decline in synchronous firing and rate of transmission of the auditory cortical neurons contributing to the auditory P300 exists. Studies are needed to further understand the impact of noise on auditory cortical processing across populations.
Keywords: Acoustic Stimulation; Aged; Aging; Auditory Cortex; Auditory Perception; Auditory Threshold; Cognition; Conference Paper; Evoked Potentials, Auditory; Female; Hearing in noise; Humans; Male; P300; Reference Values; Young Adult; adult; aged; auditory cortex; auditory evoked potential; auditory stimulation; auditory threshold; brain cell; clinical article; cognition; comparative study; convenience sample; dept.cmd; female; hearing; hearing acuity; hearing impairment; human; latent period; male; medical history; mental deterioration; noise; otoscopy; outcome assessment; peer-reviewed; physiology; priority journal; procedures; pure tone audiometry; reference value; signal noise ratio; white noise; working memory; young adult

Communication and cognition - LaPointe, Leonard L.; Stierwalt, Julie; Purdy, Mary H. (Aphasia and related neurogenic language disorders, 2018)
Rapid advances in neural imaging, particularly in regard to neural plasticity and brain changes, have resulted in an evolving neurorehabilitation paradigm for aphasia and related language disorders. Aphasia and Related Neurogenic Language Disorders has been adopted worldwide as a text for aphasia courses. This new 5th edition by Leonard LaPointe and Julie Stierwalt encompasses state-of-the-art concepts and approaches from an impressive cadre of experts who work in research labs, classrooms, clinics, and hospitals-including the world-renowned Mayo Clinic.As in previous editions, this book embraces a humanistic approach to treatment, addressing multicultural and multilinguistic considerations and social model interventions. The text encompasses a full continuum of cognitive-language disorder management-from everyday practicalities, assessment, and treatment to disorder-specific cases with evidence-based data. Additions to the 5th edition include chapters on pragmatics and discourse, telepractice, digital and electronic advances, funding and reimbursement, and comprehension, syntax, and linguistic based disorders.Key Features:A new chapter on neuroanatomical basics features exquisite illustrationsAn in-depth look at neurogenic communication disorders from Mayo Clinic provides firsthand insights on treating patients in an acute care hospital settingDiscussion and test questions, case studies, and clinical pearls offer invaluable didactic guidanceA chapter on expanded traumatic brain injury covers blast injuries and multisystem injuriesThis is the most comprehensive yet concise resource on aphasia and related disorders available today. New legions of speech language pathology students, residents, course directors, and practitioners will discover a remarkable guide on the treatment of communication disorders.
Keywords: dept.cmd

Social Pragmatic Communication and Literacy in African American English Speakers - Hyter, Yvette D.; DeJarnette, Glenda; Rivers, Kenyatta O. (Perspectives of the ASHA Special Interest Groups, 2018)
Keywords: dept.cmd; peer-reviewed

Comparing simultaneous clinical swallow evaluations and fiberoptic endoscopic evaluations of swallowing: Changing practice patterns - Leder, Steven B.; Warner, Heather L. (Perspectives of the ASHA Special Interest Groups, 2018)
Keywords: dept.cmd; peer-reviewed

Effectiveness of a preexternship hospital orientation program for graduate students in speech-language pathology - Warner, Heather; Karlberg, Amy; Purdy, Mary (Perspectives of the ASHA Special Interest Groups, 2018)
Keywords: dept.cmd; peer-reviewed

Interpersonal supports - Cook, Barbara (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Relationship enhancement methods - Cook, Barbara (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

Peer mentors for students with ASD on college campuses - Cook, Barbara; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2018)
Keywords: dept.cmd

A facilitated natural mentoring program: Young adults with autism learn to negotiate college life in a class with university students - Cook, Barbara; Weiss, Deborah; Hodge, Virginia (The ASHA Leader, 2017)
Young adults with autism learn to negotiate college life in a class with university students. © 2017 American Speech-Language-Hearing Association.
Keywords: dept.cmd

Electrophysiological Indices of Audiovisual Speech Perception in the Broader Autism Phenotype. - Irwin, Julia; Avery, Trey; Turcios, Jacqueline; Brancazio, Lawrence; Cook, Barbara; Landi, Nicole (Brain sciences, 2017)
When a speaker talks, the consequences of this can both be heard (audio) and seen (visual). A novel visual phonemic restoration task was used to assess behavioral discrimination and neural signatures (event-related potentials, or ERP) of audiovisual processing in typically developing children with a range of social and communicative skills assessed using the social responsiveness scale, a measure of traits associated with autism. An auditory oddball design presented two types of stimuli to the listener, a clear exemplar of an auditory consonant-vowel syllable /ba/ (the more frequently occurring standard stimulus), and a syllable in which the auditory cues for the consonant were substantially weakened, creating a stimulus which is more like /a/ (the infrequently presented deviant stimulus). All speech tokens were paired with a face producing /ba/ or a face with a pixelated mouth containing motion but no visual speech. In this paradigm, the visual /ba/ should cause the auditory /a/ to be perceived as /ba/, creating an attenuated oddball response; in contrast, a pixelated video (without articulatory information) should not have this effect. Behaviorally, participants showed visual phonemic restoration (reduced accuracy in detecting deviant /a/) in the presence of a speaking face. In addition, ERPs were observed in both an early time window (N100) and a later time window (P300) that were sensitive to speech context (/ba/ or /a/) and modulated by face context (speaking face with visible articulation or with pixelated mouth). Specifically, the oddball responses for the N100 and P300 were attenuated in the presence of a face producing /ba/ relative to a pixelated face, representing a possible neural correlate of the phonemic restoration effect. Notably, those individuals with more traits associated with autism (yet still in the non-clinical range) had smaller P300 responses overall, regardless of face context, suggesting generally reduced phonemic discrimination.
Keywords: Article; Audiovisual speech perception; Broader autism phenotype; Development; ERP; audiovisual aid; audiovisual equipment; audiovisual speech perception; autism; behavior; broader autism phenotype; child; clinical article; dept.cmd; dept.hls; dept.psy; development; electrophysiology; female; human; male; participant observation; phenotype; social adaptation; social competence; speech perception; stimulus; vision test

Risk of reading difficulty among students with a history of speech or language impairment: Implications for Student Support Teams - Zipoli, Richard P.; Merritt, Donna D. (Preventing School Failure: Alternative Education for Children and Youth, 2017)
Many students with a history of speech or language impairment have an elevated risk of reading difficulty. Specific subgroups of these students remain at risk of reading problems even after clinical manifestations of a speech or language disorder have diminished. These students may require reading intervention within a general education system of supports and services. The first part of this article describes three speech-language disorders that place elementary students at risk of reading problems: functional speech disorders, childhood apraxia of speech, and specific language impairment. Emphasis is given to research findings on the reading outcomes of students with these disorders. The second part of the article provides recommendations within an RTI framework that will assist Student Support Teams in identifying, monitoring, and supporting these students. © 2017 Taylor & Francis Group, LLC.
Keywords: Assessment; Language impairment; RTI; Reading disability; Speech sound disorders; dept.cmd; peer-reviewed

Unraveling difficult sentences: strategies to support reading comprehension - Zipoli, Jr., Richard P. (Intervention In School And Clinic, 2017)
The ability to understand sentences contributes to students' reading comprehension. However, many reading programs tend to underemphasize explicit instruction aimed at enhancing students' knowledge of sentence structures. Children with language impairments, students with learning disabilities, and English language learners may particularly benefit from instruction that targets potentially challenging sentence structures. This article is designed to help educators and clinicians more effectively identify and teach several sentence structures that can compromise elementary and middle school students' understanding of written text. Four types of sentence structures that may be difficult to process are introduced and systematically explored: (a) sentences with passive verb constructions, (b) adverbial clauses with temporal and causal conjunctions, (c) center-embedded relative clauses, and (d) sentences with three or more clauses. Information is presented on syntactic structures, sources of confusion, developmental considerations, assessment caveats, and instructional strategies.
Keywords: dept.cmd; peer-reviewed; reading comprehension; reading instruction; sentence comprehension; syntax

The effects of auditory training on dichotic listening: A neurological case study - McCullagh, Jennifer; Palmer, Shannon B. (Hearing, Balance and Communication, 2017)
Background: Individuals with neurological impairment have been shown to have deficits in auditory processing abilities. One auditory processing ability shown to be affected is dichotic listening. To date, limited evidence exists demonstrating the effectiveness of dichotic listening intervention on dichotic listening in individuals with neurological impairment. The purpose of this study was to determine the effects of the dichotic listening training on dichotic listening abilities over multiple training periods in an individual with a long-standing and stable neurological history. Method: This study used a case study design. Over the course of 3 years, an individual with dichotic listening deficits following a left cerebral vascular accident underwent multiple auditory training periods using a dichotic listening training paradigm. Initial assessments indicated a bilateral deficit on the Dichotic Digits test with the right ear performing more poorly than the left ear and a right ear deficit on the Dichotic Rhyme test. Training sessions took place 2–3 times per week for a period of 4–11 weeks in the years 2012, 2013 and 2014. Pre- and post-training assessments of dichotic listening and hearing in noise ability were completed for each training period. Results: Results indicated improvements in the trained (right) ear on the Dichotic Digits test following each of the three training periods. Results also indicated stable performance in the right ear on the Dichotic Rhyme test and variable performance on the Words-in-Noise (WIN) test following each training session. Performance on the Dichotic Digits test decreased slightly between training periods; however, overall performance showed improvement over time. Conclusion: These results suggest improved binaural integration abilities as measured by the Dichotic Digits test following dichotic listening training in an individual with neurological impairment. However, the effects of the training did not transfer to tasks of binaural fusion (Dichotic Rhyme test) or hearing in noise (WIN test) tasks. © 2016 International Association of Physicians in Audiology.
Keywords: Article; Auditory training; adult; aphasia; auditory evoked potential; auditory processing disorder; carotid artery obstruction; case report; cerebrovascular accident; dept.cmd; dichotic listening; distortion product otoacoustic emission; follow up; general condition improvement; human; left hemisphere; male; neurological impairment; noise; nuclear magnetic resonance imaging; patient referral; peer-reviewed; priority journal; pure tone audiometry; speech and language rehabilitation; speech audiometry; speech language pathologist; training; tympanometry